A cross-scale multi-level graphene composite absorbing material and preparation method thereof

By growing graphene and transition metal sulfide on foam copper templates, a multi-layer graphene composite absorbing material is formed, which solves the shortcomings of existing absorbing materials in electromagnetic field protection and mechanical bearing, and achieves ultra-wide frequency and high-efficiency absorbing and Combination of excellent mechanical properties.

CN113871896BActive Publication Date: 2025-02-11SOUTHEAST UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111096635.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-17
Publication Date
2025-02-11
Estimated Expiration
2041-09-17

AI Technical Summary

Technical Problem

In the demands of strong electromagnetic field protection, thinning and lightweighting, existing absorbing materials have problems such as high density, poor high-temperature characteristics, poor corrosion resistance, poor impedance matching, narrow absorption frequency band, and poor absorption performance, and it is difficult to meet the requirements of high electromagnetic field protection, thinning and lightweighting. Requirements for wide-band strong stealth, mechanical load-bearing and thin design.

Method used

The multi-layer graphene composite absorbing material is adopted, and the preparation method includes laser texture treatment of foam copper plates, growing graphene and transition metal sulfides, removing structural templates and assembling multi-layer heterogeneous composite material plates to form Superstructured porous graphene-based heterogeneous composite material.

Benefits of technology

It realizes the ultra-wideband efficient wave absorption performance and excellent mechanical load-bearing capacity, and has tunable wave absorption properties to meet the needs of thin and lightweight, wideband stealth and efficient load-bearing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113871896B_ABST
    Figure CN113871896B_ABST
Patent Text Reader

Abstract

The present invention provides a cross-scale multi-level graphene composite wave absorbing material and a preparation method thereof, the preparation method comprising the following steps: step 10) laser texturing a foam copper plate to obtain a structural template with a surface superstructure; step 20) using ALD technology to grow graphene and transition metal sulfide on the structural template respectively; step 30) using an etching process to remove the structural template to obtain a graphene-transition metal sulfide heterogeneous composite material plate; step 40) assembling at least two layers of graphene-transition metal sulfide heterogeneous composite material plates to obtain a cross-scale multi-level graphene composite wave absorbing material. The cross-scale multi-level graphene composite wave absorbing material prepared by the present invention ensures excellent mechanical properties while achieving ultra-wideband efficient wave absorption, and has tunable wave absorption properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of micro-nano manufacturing and absorbing materials, and specifically relates to a cross-scale multi-level graphene composite absorbing material and a preparation method thereof. Background Art

[0002] Traditional absorbing materials (such as metal powders) mostly have disadvantages such as high density, poor high temperature characteristics, poor corrosion resistance, or poor impedance matching, narrow absorbing band, and poor absorbing performance. Graphene is a new type of two-dimensional carbon nanomaterial with a large specific surface area, adjustable working surface, ultra-high mechanical strength, extremely high thermal conductivity, excellent carrier mobility, and a special electromagnetic wave action mechanism. The development of new absorbing materials based on graphene is expected to replace traditional materials, effectively protecting against strong electromagnetic fields while meeting the needs of thin and lightweight use.

[0003] On the one hand, the basic properties of the material largely determine its wave absorption performance. Theoretical studies have shown that defects in the graphene lattice structure and oxygen-containing groups on the surface of the graphene sheets can not only improve the impedance matching characteristics of graphene and promote the conversion of energy from adjacent states to the Fermi level, but also produce defect polarization relaxation and functional group electronic dipole polarization relaxation, thereby improving the electromagnetic wave loss characteristics of graphene. However, the wave absorption characteristics of pure graphene materials are not satisfactory. This is because the dielectric constant and magnetic permeability of graphene materials differ greatly, the impedance matching performance is poor, and electromagnetic waves are difficult to penetrate into the material, so the wave absorption performance of graphene cannot be fully utilized.

[0004] On the other hand, the structural characteristics of the material will also have an important impact on the optimization of the wave absorption performance. Graphene composite materials with three-dimensional structures formed by overlapping two-dimensional graphene sheets have received more and more attention in the field of wave absorption. Practical application scenarios require that the stealth structure has broadband strong stealth performance, mechanical bearing performance and thin design at the same time, while thin structure design, broadband stealth and mechanical bearing performance are three-way contradictions that are difficult to meet at the same time. Graphene composite materials with three-dimensional structures, such as graphene composite aerogels, can achieve effective wave absorption while ensuring excellent mechanical properties. It is particularly important to point out that the three-dimensional graphene has a porous structure inside, a low volume density, and a relatively small dielectric constant. Therefore, it is easier to absorb electromagnetic waves in a wider frequency range. In addition to the internal microstructure, the idea of ​​metamaterials and the design of superstructures at the macroscopic scale on the surface can also improve the wave absorption properties. Through reasonable and orderly structural design, the surface of the superstructure can show unique response properties to electromagnetic waves. Combining the design of microstructures with the design of macrostructures is expected to achieve ultra-wideband efficient wave absorption. At present, there are few achievements in this regard, and further in-depth research is needed. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a cross-scale multi-level graphene composite absorbing material and a preparation method thereof, which can ensure excellent mechanical properties while achieving ultra-wideband efficient absorbing and have tunable absorbing properties.

[0006] In order to solve the above technical problems, on the one hand, the present invention provides a method for preparing a cross-scale multi-level graphene composite absorbing material, comprising the following steps:

[0007] Step 10) performing laser texturing treatment on the foam copper plate to obtain a structural template with a surface superstructure;

[0008] Step 20) using ALD technology to grow graphene and transition metal sulfide on the structure template respectively;

[0009] Step 30) removing the structural template by etching process to obtain a graphene-transition metal sulfide heterogeneous composite material plate;

[0010] Step 40) Assemble at least two layers of graphene-transition metal sulfide heterogeneous composite material plates to obtain a cross-scale multi-level graphene composite absorbing material.

[0011] As a further improvement of the embodiment of the present invention, the porosity of the structural template obtained in step 10) is 50-98%, the pore size is 0.01-1 mm, and the thickness is 0.15-3 mm.

[0012] As a further improvement of the embodiment of the present invention, the surface superstructure of the structural template obtained in step 10) is one of annular steps, polygonal steps and combined steps.

[0013] As a further improvement of the embodiment of the present invention, in the step 20), benzene is used as a carbon source, hydrogen is used as a reducing gas, and nitrogen or argon is used as a cleaning gas for growing graphene; the heating temperature is 200 to 800° C., and the heating time is 1 to 6 hours.

[0014] As a further improvement of an embodiment of the present invention, in step 20), MoCl5, ReCl5 or WCl6 is used as a transition metal source, H2S is used as a reducing gas, and nitrogen or argon is used as a cleaning gas to grow transition metal sulfides; the heating temperature is 300 to 1000°C, and the heating time is 1 to 6 hours.

[0015] As a further improvement of the embodiment of the present invention, in the step 30), the etching process uses FeCl3 solution as the etching solution, the etching temperature is 20 to 50°C, and the etching time is 0.5 to 6 hours.

[0016] As a further improvement of the embodiment of the present invention, in the step 40), at least two layers of graphene-transition metal sulfide heterogeneous composite material plates are assembled using an adhesive; the adhesive is one of polyurethane, polymethyl methacrylate, polystyrene, epoxy resin and silicone resin.

[0017] As a further improvement of the embodiment of the present invention, in the step 40), the number of layers of the graphene-transition metal sulfide heterogeneous composite material plate is 2 to 10, and the total thickness is 0.5 to 10 mm.

[0018] In a second aspect, an embodiment of the present invention provides a cross-scale multi-level graphene composite absorbing material, which is prepared using the above-mentioned preparation method.

[0019] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0020] The cross-scale multi-level graphene composite absorbing material and preparation method thereof provided in the embodiment of the present invention are based on the foam copper sacrificial template method and multi-source same-cavity ALD technology, and cross-scale coupling optimization and multi-level structural performance comprehensive design of various factors in the design and manufacturing process such as the number of graphene layers, porous skeleton size, heterojunction type, surface superstructure, and multi-level combination mode are carried out from the three scale levels of micro, nano, and macro to construct a new system of porous graphene-based heterogeneous composite material superstructure absorbing. Compared with traditional absorbing materials, the cross-scale multi-level graphene composite absorbing material in the embodiment of the present invention can achieve the fusion of ultra-wideband absorbing and strong mechanical bearing due to the coupling and design of microstructure and macrostructure, and has tunable absorbing properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Schematic diagram of the process of preparing the cross-scale multi-level graphene composite absorbing material in Example 1 of the present invention;

[0022] Figure 2 Schematic diagram of a multi-source same-chamber ALD system in Example 1 of the present invention. DETAILED DESCRIPTION

[0023] The technical solution of the present invention is described in detail below.

[0024] The embodiment of the present invention provides a method for preparing a cross-scale multi-level graphene composite absorbing material, comprising the following steps:

[0025] Step 10) laser texturing is performed on the foam copper plate to obtain a structural template with a surface superstructure.

[0026] Step 20) Atomic layer deposition (ALD) technology is used to grow graphene on the foam copper skeleton of the structural template and to grow transition metal sulfide in the foam copper gap of the structural template. The transition metal sulfide includes one or more of MoS2, ReS2, and WS2.

[0027] Step 30) The structural template is removed by etching process to obtain a graphene-transition metal sulfide heterogeneous composite material plate.

[0028] Step 40) assembling at least two layers of graphene-transition metal sulfide heterogeneous composite material plates prepared through steps 10) to 30) to obtain a cross-scale multi-level graphene composite absorbing material.

[0029] The above-mentioned embodiment method, by combining the foam copper sacrificial template method and the multi-source same-cavity ALD technology, performs integrated design and preparation of the structure and function of the graphene composite absorbing material from three scale levels, namely, the number of graphene layers and heterojunction types at the nanoscale, the porosity and pore size of the three-dimensional porous structure at the microscale, and the surface superstructure and multi-level combination mode at the macroscale, so as to realize a new strategy for manufacturing absorbing materials that integrates ultra-wideband absorption and mechanical bearing. The cross-scale multi-level graphene composite absorbing material prepared by the preparation method of the present invention, the mutually cross-linked graphene sheets constitute a porous skeleton, thereby forming a connected conductive network, which can consume electromagnetic wave energy through conductive loss. The transition metal sulfide grown on the graphene surface forms a two-dimensional heterostructure with the graphene. By growing different types of transition metal sulfides, the electronic properties of the heterojunction can be adjusted, and the electromagnetic wave can be consumed through polarization loss. The transition metal sulfide filled in the pores can support the entire structure, and the combination with the graphene skeleton with excellent mechanical properties greatly improves the overall mechanical bearing capacity. Transition metal sulfide itself can be used as a dielectric material to dissipate electromagnetic waves and enhance microwave absorption capacity. At the same time, graphene and transition metal sulfide are both low-density two-dimensional materials, which makes the entire system lightweight. The surface superstructure can cause electromagnetic waves to resonate through a periodic subwavelength structure, thereby enhancing the consumption of electromagnetic wave energy. Multilayer graphene-transition metal sulfide heterogeneous composite material plates with surface superstructures are combined together through an adhesive, and the layers with different electromagnetic parameters can be arranged in order as needed to obtain a graphene composite absorbing material with ultra-wideband and tunable absorbing ability. Compared with existing absorbing materials, the absorbing material of the present invention has the cross-scale nature of material preparation and the designability of structural function integration, and at the same time has the functions and characteristics of thinness and lightness, broadband stealth, and efficient load-bearing.

[0030] Preferably, the porosity of the structural template obtained in step 10) is 50-98%, the pore size is 0.01-1 mm, and the thickness is 0.15-3 mm. In this embodiment, the structural template of the above specifications is conducive to the growth of graphene on the surface and the filling of transition metal sulfides in the gaps, thereby forming a core skeleton composed of a porous interconnected structure of graphene and a supporting structure filled with transition metal sulfides, and obtaining a graphene-transition metal sulfide heterogeneous composite material plate with both absorbing performance and mechanical bearing.

[0031] Preferably, the surface superstructure of the structural template obtained in step 10) is one of an annular step, a polygonal step and a combined step. The surface superstructure of this embodiment manipulates electromagnetic waves through a periodic sequence of geometric figures to consume electromagnetic waves, including but not limited to plane geometric figures, three-dimensional step structures, three-dimensional cone structures, etc. Surface superstructures of different shapes can be selected according to the frequency band of the required electromagnetic waves, and the size of the shape can be designed to promote the consumption of electromagnetic waves.

[0032] The laser power used in the laser texturing process in step 10) is 10-150 W, the scanning speed is 100-2000 mm / min, and the scanning times are 5-30. The above laser parameter range is conducive to the rapid and accurate manufacture of surface superstructures and the maintenance of geometrical dimensional accuracy.

[0033] Step 20) Use Figure 2 The multi-source same-chamber ALD shown includes a reaction chamber and four source gas supply paths, which can introduce gases into the reaction chamber separately or simultaneously. The source gas supply paths include a carbon source, a transition metal source and two reducing gas sources.

[0034] Preferably, when growing graphene, benzene is used as a carbon source, hydrogen as a reducing gas, and nitrogen or argon as a cleaning gas. The heating temperature is 200-800°C, and the heating time is 1-6h. The pulse parameters of benzene and hydrogen are that the pulse time of benzene is 0.1-3s, and the pulse time of hydrogen is 1-15s. After each precursor pulse, nitrogen or argon cleaning is performed for 10-60s, and 1-100 pulse cycles are performed. The precursor benzene is heated to 100-200°C, the hydrogen precursor is kept at room temperature, and is respectively introduced into the reaction chamber of the atomic layer deposition equipment at a carrier gas flow rate of 20-100sccm. The multi-source same-chamber ALD growth of graphene adopts the technical parameters in the above range, which is conducive to the formation of high-quality graphene sheets with high crystallinity, good sheet continuity and large area, and is conducive to the cross-linking between graphene to form a good conductive network and mechanical bearing structure.

[0035] Preferably, when growing transition metal sulfides, MoCl5, ReCl5 or WCl6 is used as a transition metal source, H2S is used as a reducing gas, and nitrogen or argon is used as a cleaning gas. The heating temperature is 300-1000°C, and the heating time is 1-6h. The pulse time of the transition metal source is 0.1-3s, and the pulse time of H2S is 0.5-10s. After each precursor pulse, nitrogen or argon cleaning is performed for 20-60s, and 25-1000 pulse cycles are performed. The precursor transition metal source is heated to 200-300°C, and the H2S precursor is kept at room temperature, and is introduced into the reaction chamber of the atomic layer deposition equipment at a carrier gas flow rate of 20-100sccm. The multi-source same-chamber ALD growth of transition metal sulfides using the technical parameters within the above range is conducive to the formation of high-quality two-dimensional transition metal sulfide sheets with high crystallinity, good sheet continuity and large area, which is conducive to the formation of a two-dimensional heterostructure with graphene sheets, thereby enhancing the polarization loss capacity of the composite material.

[0036] Preferably, in step 30), the etching process uses FeCl3 solution or other copper etching solution, the etching temperature is 20-50°C, and the etching time is 0.5-6 hours. After etching, use excess deionized water for sufficient cleaning. This example uses the above etching process parameters, which is conducive to the rapid removal of the structural template without affecting the quality of graphene and transition metal sulfides.

[0037] Preferably, in step 40), at least two layers of graphene-transition metal sulfide heterogeneous composite material plates are assembled using an adhesive. The adhesive is one of polyurethane, polymethyl methacrylate, polystyrene, epoxy resin and silicone resin. In this example, the use of an adhesive can tightly combine the multiple layers of heterogeneous composite material plates together to ensure the mechanical properties of the overall absorbing material.

[0038] Preferably, in step 40), the number of layers of the graphene-transition metal sulfide heterogeneous composite material plate is 2 to 10 layers, and the total thickness is 0.5 to 10 mm. The graphene-transition metal sulfide heterogeneous composite material plate used in the assembly process of the cross-scale multi-level graphene composite absorbing material can be prepared by steps 10) to 30) for foam copper plates of different specifications or the same specifications. The graphene-transition metal sulfide heterogeneous composite material plate has different properties according to the differences in the number of graphene layers and heterojunction types at the nanoscale, the porosity and pore size of the three-dimensional porous structure at the microscale, and the surface superstructure at the macroscale. The arrangement order of the multi-layer graphene-transition metal sulfide heterogeneous composite material is arbitrary when the cross-scale multi-level graphene composite absorbing material is assembled. The number of layers and thickness of the graphene-transition metal sulfide heterogeneous composite material plate used for assembly in this example can achieve broadband absorption while ensuring low thickness.

[0039] An embodiment of the present invention also provides a cross-scale multi-level graphene composite absorbing material, which is prepared using the above-mentioned preparation method.

[0040] The cross-scale multi-level graphene composite absorbing material of the embodiment of the present invention is formed by arranging multiple layers of graphene-transition metal sulfide heterogeneous composite material plates. The graphene-transition metal sulfide heterogeneous composite material plates have a core skeleton composed of a graphene porous interconnected structure and a support structure filled with transition metal sulfides, and have a super structure on the surface.

[0041] Four examples are provided below to specifically illustrate the process of the preparation method of the embodiment of the present invention and the obtained cross-scale multi-level graphene composite absorbing material.

[0042] Example 1

[0043] The cross-scale multi-layer graphene composite absorbing material is prepared by the following steps:

[0044] (1) The copper foam plate was laser textured to obtain a structural template with a surface superstructure. Three types of copper foam plates were used, all with a porosity of 80%, pore sizes of 0.1 mm, 0.5 mm and 1 mm, and a thickness of 0.5 mm. The laser power used for the laser texturing treatment was 20 W, the scanning speed was 500 mm / min, and the number of scans was 20 times. The surface superstructures obtained after the laser texturing treatment were all annular step structures.

[0045] (2) Use a multi-source same-chamber ALD system to grow graphene on a foam copper skeleton. Multi-source same-chamber ALD growth of graphene uses benzene as the carbon source, hydrogen as the reducing gas, and argon as the cleaning gas. The ALD reaction chamber heating temperature is 400°C, and the heating time is 5h. The benzene and hydrogen pulse parameters are a benzene pulse time of 0.5s and a hydrogen pulse time of 5s. After each precursor pulse, an argon purge is performed for 60s, and 20 pulse cycles are performed. The precursor benzene is heated to 200°C, and the hydrogen precursor is kept at room temperature, and is introduced into the reaction chamber of the atomic layer deposition equipment at a carrier gas flow rate of 80sccm.

[0046] (3) Use a multi-source same-chamber ALD system to grow transition metal sulfides to fill the pores of the copper foam. The transition metal sulfide used is MoS2. Multi-source same-chamber ALD growth of transition metal sulfides uses MoCl5 as the transition metal source, H2S as the reducing gas, and argon as the cleaning gas. The ALD reaction chamber heating temperature is 600°C and the heating time is 4h. The pulse time of the transition metal source used is 0.5s, and the pulse time of H2S is 1s. After each precursor pulse, an argon purge is performed for 60s, and 800 pulse cycles are performed. The precursor transition metal source is heated to 210°C, the H2S precursor is kept at room temperature, and is introduced into the reaction chamber of the atomic layer deposition equipment at a carrier gas flow rate of 80sccm.

[0047] (4) Based on the etching process, the structural template is removed to obtain a three-dimensional porous structure of a graphene-transition metal sulfide heterogeneous composite material plate. The etching solution used in the etching process is FeCl3, the etching temperature is 30°C, and the etching time is 4 hours. After the etching process is completed, an excess of deionized water is used for sufficient cleaning.

[0048] (5) The graphene-transition metal sulfide heterogeneous composite material plates obtained from templates of different specifications are assembled using an adhesive to obtain a cross-scale multi-level graphene composite absorber. The adhesive used in the assembly process is polymethyl methacrylate. The graphene-transition metal sulfide heterogeneous composite material used for assembly has a total of 3 layers, which are arranged in order from low to high pore size, and the total thickness after assembly is 3 mm.

[0049] Preparation process flow Figure 1 As shown in Figure 1 It can be seen that the cross-scale multi-level graphene composite absorbing material prepared in Example 1 can arrange the graphene-transition metal sulfide heterogeneous composite material plates in different sequences as needed, so that the overall absorbing performance has strong designability. At the same time, the overall structure spans the three scales of nanometer, micrometer and macro, and the preparation process has a strong integration.

[0050] Example 2

[0051] The cross-scale multi-layer graphene composite absorbing material is prepared by the following steps:

[0052] (1) The copper foam plate was laser textured to obtain a structural template with a surface superstructure. There are two types of copper foam plates used, with porosities of 60% and 80%, pore sizes of 0.2 mm and 0.6 mm, and thickness of 1 mm. The laser power used for laser texturing was 50 W, the scanning speed was 200 mm / min, and the number of scans was 10. The surface superstructures obtained after laser texturing were all conical step structures.

[0053] (2) Use a multi-source same-chamber ALD system to grow graphene on a foam copper skeleton. Multi-source same-chamber ALD growth of graphene uses benzene as the carbon source, hydrogen as the reducing gas, and nitrogen as the cleaning gas. The ALD reaction chamber heating temperature is 300°C, and the heating time is 4h. The benzene and hydrogen pulse parameters are 0.2s for benzene and 3s for hydrogen. After each precursor pulse, a 30s nitrogen purge is performed, and 30 pulse cycles are performed. The precursor benzene is heated to 210°C, and the hydrogen precursor is kept at room temperature, and they are respectively introduced into the reaction chamber of the atomic layer deposition equipment at a carrier gas flow rate of 50sccm.

[0054] (3) Use a multi-source same-chamber ALD system to grow transition metal sulfides to fill the pores of the copper foam. The transition metal sulfide used is ReS2. The multi-source same-chamber ALD system to grow transition metal sulfides uses ReCl5 as the transition metal source, H2S as the reducing gas, and nitrogen as the cleaning gas. The heating temperature of the ALD reaction chamber is 800°C, and the heating time is 3h. The pulse time of the transition metal source is 1s, and the pulse time of H2S is 2s. After each precursor pulse, a 50s nitrogen purge is performed, and 600 pulse cycles are performed. The precursor transition metal source is heated to 220°C, and the H2S precursor is kept at room temperature and introduced into the reaction chamber of the atomic layer deposition equipment at a carrier gas flow rate of 50sccm.

[0055] (4) Based on the etching process, the structural template is removed to obtain a graphene-transition metal sulfide heterogeneous composite material plate with a three-dimensional porous structure. The etching solution used in the etching process is a copper etching solution, the etching temperature is 40° C., and the etching time is 3 hours. After the etching process is completed, an excess of deionized water is used for sufficient cleaning.

[0056] (5) The graphene-transition metal sulfide heterogeneous composite material plates obtained from templates of different specifications are assembled using an adhesive to obtain a cross-scale multi-level graphene composite absorber. The adhesive used in the assembly process is epoxy resin. The graphene-transition metal sulfide heterogeneous composite material used for assembly has a total of 6 layers, 3 layers of each of the two porosities and pore sizes, 3 layers with a porosity and pore size of 60% and 0.2 mm on the top, and the other 3 layers are combined at the bottom, and the total thickness after assembly is 8.5 mm.

[0057] Example 3

[0058] The cross-scale multi-layer graphene composite absorbing material is prepared by the following steps:

[0059] (1) Laser texturing is performed on the copper foam plate to obtain a structural template with a surface superstructure. The copper foam plate used has a porosity of 90%, a pore size of 0.3 mm, and a thickness of 1.5 mm. The laser power used for the laser texturing treatment is 100 W, the scanning speed is 1000 mm / min, and the number of scans is 5 times. The surface superstructures obtained after the laser texturing treatment are all triangular step structures.

[0060] (2) Use a multi-source same-chamber ALD system to grow graphene on a foam copper skeleton. Multi-source same-chamber ALD growth of graphene uses benzene as the carbon source, hydrogen as the reducing gas, and argon as the cleaning gas. The ALD reaction chamber heating temperature is 800°C, and the heating time is 6h. The benzene and hydrogen pulse parameters are a benzene pulse time of 1.5s and a hydrogen pulse time of 15s. After each precursor pulse, an argon purge is performed for 45s, and 30 pulse cycles are performed. The precursor benzene is heated to 180°C, and the hydrogen precursor is kept at room temperature, and is introduced into the reaction chamber of the atomic layer deposition equipment at a carrier gas flow rate of 100sccm.

[0061] (3) Use a multi-source same-chamber ALD system to grow transition metal sulfides to fill the pores of the foamed copper. The transition metal sulfide used is MoS2. The multi-source same-chamber ALD system uses MoCl5 as the transition metal source, H2S as the reducing gas, and argon as the cleaning gas to grow the transition metal sulfide. The heating temperature of the ALD reaction chamber used is 700°C, and the heating time is 6h; the pulse time of the transition metal source used is 2s, and the pulse time of H2S is 8s; after each precursor pulse, argon gas cleaning is performed for 60s, and 1000 pulse cycles are performed; the precursor transition metal source is heated to 260°C, and the H2S precursor is kept at room temperature and introduced into the reaction chamber of the atomic layer deposition equipment at a carrier gas flow rate of 100sccm.

[0062] (4) Based on the etching process, the foam copper template is removed to obtain a three-dimensional porous graphene-transition metal sulfide heterogeneous composite material plate. The etching solution used in the etching process is FeCl3, the etching temperature is 50°C, and the etching time is 3 hours. After the etching process is completed, an excess of deionized water is used for sufficient cleaning.

[0063] (5) Assembling the graphene-transition metal sulfide heterogeneous composite material plates using an adhesive to obtain a cross-scale multi-level graphene composite absorber. The adhesive used in the assembly process is silicone resin. The graphene-transition metal sulfide heterogeneous composite material used for assembly has a total of 5 layers, and the total thickness after assembly is 8.5 mm.

[0064] Example 4

[0065] The cross-scale multi-layer graphene composite absorbing material is prepared by the following steps:

[0066] (1) The copper foam plate was laser textured to obtain a structural template with a surface superstructure. There are two types of copper foam plates used, with porosities of 50% and 98%, pore sizes of 1 mm and 0.01 mm, and thickness of 2 mm. The laser power used for laser texturing was 150 W, the scanning speed was 1500 mm / min, and the number of scans was 30. The surface superstructures obtained after laser texturing were a ring-shaped stepped structure for the former and a triangular stepped structure for the latter.

[0067] (2) Use a multi-source same-chamber ALD system to grow graphene on a foam copper skeleton. The multi-source same-chamber ALD system used to grow graphene uses benzene as the carbon source, hydrogen as the reducing gas, and argon as the cleaning gas. The ALD reaction chamber heating temperature is 700°C, and the heating time is 5.5h. The benzene and hydrogen pulse parameters are 3s for benzene and 10s for hydrogen. After each precursor pulse, an argon purge is performed for 60s, and 10 pulse cycles are performed. The precursor benzene is heated to 190°C, and the hydrogen precursor is kept at room temperature, and they are respectively introduced into the reaction chamber of the atomic layer deposition equipment at a carrier gas flow rate of 90sccm.

[0068] (3) Use a multi-source same-chamber ALD system to grow transition metal sulfides to fill the pores of the foamed copper. The transition metal sulfide used is WS2. The multi-source same-chamber ALD system to grow transition metal sulfides uses WCl6 as the transition metal source, H2S as the reducing gas, and argon as the cleaning gas. The heating temperature of the ALD reaction chamber is 1000°C, and the heating time is 5h. The pulse time of the transition metal source is 3s, and the pulse time of H2S is 10s. After each precursor pulse, an argon purge is performed for 60s, and 50 pulse cycles are performed. The precursor transition metal source is heated to 300°C, and the H2S precursor is kept at room temperature and introduced into the reaction chamber of the atomic layer deposition equipment at a carrier gas flow rate of 100sccm.

[0069] (4) Based on the etching process, the structural template is removed to obtain a three-dimensional porous graphene-transition metal sulfide heterogeneous composite material. The etching solution used in the etching process is FeCl3, the etching temperature is 20°C, and the etching time is 6 hours. After the etching process is completed, an excess of deionized water is used for sufficient cleaning.

[0070] (5) The graphene-transition metal sulfide heterogeneous composite material plates obtained from templates of different specifications are assembled using an adhesive to obtain a cross-scale multi-level graphene composite absorber. The adhesive used in the assembly process is polyurethane. The graphene-transition metal sulfide heterogeneous composite material plates used for assembly have a total of 4 layers. The 4 layers of heterogeneous composite material plates are alternately combined in the manner of a layer with high porosity, a layer with low porosity, a layer with high porosity, and a last layer with low porosity. The total thickness after assembly is 10 mm.

[0071] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above specific embodiments. The above specific embodiments and the description in the specification are only for further illustrating the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of the present invention to be protected is defined by the claims and their equivalents.

Claims

1. A method for preparing a cross-scale multi-level graphene composite absorbing material, characterized in that: The following steps are involved: Step 10) performing laser texturing on the foam copper plate to obtain a structural template with a surface superstructure; Step 20) using ALD technology to grow graphene and transition metal sulfide on the structure template respectively; Step 30) removing the structural template by etching process to obtain a graphene-transition metal sulfide heterogeneous composite material plate; Step 40) assembling at least two layers of graphene-transition metal sulfide heterogeneous composite material plates to obtain a cross-scale multi-level graphene composite absorbing material; The porosity of the structural template obtained in step 10) is 50-98%, the pore size is 0.01-1 mm, and the thickness is 0.15-3 mm.

2. The preparation method according to claim 1, characterized in that: The surface superstructure of the structural template obtained in step 10) is one of annular steps, polygonal steps and combined steps.

3. The preparation method according to claim 1, characterized in that: In the step 20), benzene is used as a carbon source, hydrogen is used as a reducing gas, and nitrogen or argon is used as a cleaning gas for growing graphene; the heating temperature is 200-800° C., and the heating time is 1-6 h.

4. The preparation method according to claim 1, characterized in that: In the step 20), MoCl5, ReCl5 or WCl6 is used as a transition metal source, H2S is used as a reducing gas, and nitrogen or argon is used as a cleaning gas to grow transition metal sulfides; the heating temperature is 300-1000°C, and the heating time is 1-6 hours.

5. The preparation method according to claim 1, characterized in that: In the step 30), the etching process uses FeCl3 solution as the etching solution, the etching temperature is 20-50°C, and the etching time is 0.5-6 hours.

6. The preparation method according to claim 1, characterized in that: In the step 40), at least two layers of graphene-transition metal sulfide heterogeneous composite material plates are assembled using an adhesive; the adhesive is one of polyurethane, polymethyl methacrylate, polystyrene, epoxy resin and silicone resin.

7. The preparation method according to claim 1, characterized in that: In the step 40), the number of layers of the graphene-transition metal sulfide heterogeneous composite material plate is 2 to 10, and the total thickness is 0.5 to 10 mm.

8. A cross-scale multi-level graphene composite absorbing material, characterized in that: The preparation method is described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Application of graphene and molybdenum disulfide composite material as electromagnetic wave absorption material

    CN105428820A

  • Large area ultra-thin graphene / MoS2 superlattice heterostructure material

    CN106409957A